Seismic characteristics of Palaeocene carbonate buildups in SE Ajdabiya Trough, Sirt Basin, Libya - Yahia A. Salem; Naser A. Altoumi; Intesar A. Haman (Surman Journal of Science and Technology, 2024)
The Palaeocene section in the SE part of Ajdabiya Trough in the eastern Sirtbasin consists of a carbonate platform, which developed, in response of rapid Lower Tertiary regional subsidence, which cause Deep–water conditions in the area and widespread marine transgression following Cenomanian rifting. Seismic sections show evidence of a number of carbonate plays (reef), particularly around the trough margins. The principal hydrocarbon reservoir in the study area is Upper Sabil, which is sealed by Harash lime mudstone. The integration of seismic and borehole data was used to develop a stratigraphic framework for the Palaeocene reefs in the area and interpret seismic variations caused by geological changes. Synthetic seismogram available in some wells used to identify the stratigraphy and to predict how stratigraphic variations may affect a seismic event. The synthetics were based mainly upon velocity changes since the relative effect of density is small in the majority of sediments. The tied between the seismic sections and the synthetic constructed in the borehole close to the seismic line show an acceptable agreement with small misties. The interpreted seismic sections illustrated clearly the onlap of the Harash shale on the delineation margins of the limestone buildup, consequently, the seismic facies changes between the reef and the adjacent strata identified by lateral changes in reflection properties. The reef body shows a chaotic reflection character. The established time structure maps of top Sheterat and Kheir (upper Palaoecene) sequences which below and over the reef respectively as well as the structure maps of the Eocene package both Gir (Lower Eocene) and Gialo (Upper Eocene) have indicated dip towards the north.The overlying sediments (Kheir Formation) develop a drape over the reef about 7 msec. Part of this can be attributed to depositional thinning of Kheir strata on to the reef, but the greater part is due to differential compaction, the pull–down velocity was revealed in some seismic sections cross the buildups as a result of the slower interval velocities of the sedimentpackage underneath the reef, which may relate to the high limestone porosity.